Hydrodynamic character of internal-loop airlift reactor - LU Gang; ZHENG Ping (浙江大学学报. 农业与生命科学版, 2003)
Gas holdup and liquid circulation velocity are the mostly important hydrodynamic characters and state parameters of internal-loop airlift reactor. In this paper, the influence of gas holdup and liquid circulation velocity on the performance of the reactor is analyzed, the models of gas holdup and liquid circulation velocity are reviewed, the factors which affect the two parameters are discussed.